Semantic and Ecological Analysis of Traditional Healing in Surau Simaung Manuscript (Code: DS004300028) - Nadhifa Indana Zulfa Rahman; Aalaa Hilyati (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to analyze the vocabulary of nature in the manuscript from the Surau Simaung collection through a lexical semantic approach, while also providing an ecological critique of the traditional healing practices reflected in the text. Semantic analysis is used to uncover the structure and meaning of vocabulary related to natural elements, while the ecological critique focuses on the reflection of the consequences of natural resource exploitation recorded in past practices. The results show that although the manuscript contains rich traditional knowledge, the intensive use of flora and fauna, including the use of certain animal species such as the pukang, reflects the limited ecological understanding of its time. These findings emphasize the importance of a critical approach to cultural heritage—not to mimic it literally, but to explore ethical values in building a more harmonious and sustainable relationship with nature. Thus, this research enriches lexical semantic studies while encouraging the formation of ecological awareness based on local wisdom.